2021
DOI: 10.1097/prs.0000000000008636
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and Risk of Cleft Lip and Palate: An Analysis of United States Birth Data

Abstract: rofacial clefts-cleft lip with or without cleft palate and cleft palate only-are among the most common congenital anomalies in the United States and the world. 1,2 Children born with orofacial clefts may experience significant long-term health sequelae, including dental and speech pathologies and stigmatizing appearance differences, even after reconstructive surgery. 3,4 Ample research has explored the multifactorial etiology of orofacial clefts, including disparities in incidence across populations. [5][6][7]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 70 publications
5
23
0
1
Order By: Relevance
“…11 Children who were born in families with limited resources often experienced delayed care and poor treatment outcomes, causing poor functional and esthetic outcomes, which in turn will affect employability during adulthood, thus creating a cycle of impoverishment. 12 The success of ABG surgery relied on several factors, such as the age of ABG initiation, graft resorption, surgeon's experience, and periodontal health. Increased age at grafting was associated with increased graft resorption, contributing to poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Children who were born in families with limited resources often experienced delayed care and poor treatment outcomes, causing poor functional and esthetic outcomes, which in turn will affect employability during adulthood, thus creating a cycle of impoverishment. 12 The success of ABG surgery relied on several factors, such as the age of ABG initiation, graft resorption, surgeon's experience, and periodontal health. Increased age at grafting was associated with increased graft resorption, contributing to poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Upadhyaya stated that there was a significant correlation between the patient’s age during their first medical consultation with the socioeconomic status of the family, literacy status of the parents, and distance from the hospital 11. Children who were born in families with limited resources often experienced delayed care and poor treatment outcomes, causing poor functional and esthetic outcomes, which in turn will affect employability during adulthood, thus creating a cycle of impoverishment 12…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, girls were more likely than boys to achieve ≥86% correct consonants. This could be explained by the fact that cleft palate involving the lip is more common in males and cleft palate only in females [ 36 ], with the risk of consonant errors being higher in cases with more extended clefts.…”
Section: Discussionmentioning
confidence: 99%
“…Achieving reproductive health and access to preconception and prenatal care under SDG-3 targets will reduce the prevalence of birth defects and associated pre-and post-natal mortality. By attaining free, equitable education (SDG-4), all children with birth defects will receive quality education which By 2030, eradicate extreme poverty for all people everywhere, currently measured as people living on less than $1.25 a day • Poverty and low socio-economic status are associated with an increased risk of birth defects and mortality due to birth defects (Cornel, 2000) • Socioeconomic deprivation at a community-level increases the risk of mortality in children with heart defects (Kucik et al, 2014) • Poverty is associated with orofacial birth defects (Vu et al, 2022) • There is a higher burden of birth defects and unmet need for medical and surgical care among individuals living with birth defects in LMICs (Lakhoo, 2020;Yousef et al, 2019) • Poverty is associated with lower survival among infants and children with birth defects (Hinton et al, 2017) • Legally mandated income security programs have shown to reduce poverty rates, benefit families, and improve child health and well-being (Robinson et al, 2020) SDG 2 Zero Hunger…”
Section: Sustainable Development Goals and Birth Defectsmentioning
confidence: 99%
“…• Improving infrastructure will promote accessibility and mobility for individuals with birth defects and disabilities(Boyle & Cordero, 2005;Rimmer et al, 2005) • Economic development will have a positive impact on poverty and hence reduce poverty related birth defects(Vu et al, 2022) • A lack of affordable and accessible transportation serves as a common barrier for essential healthcare for people with birth defects(Ames et al, 2021) • Investment in accessible health care infrastructure would increase ease of access to essential services for individuals with disability due to birth defects (Moscoso-Porras et al, 2019)• Increasing technological capabilities will create opportunities for online and mHealth tools to improve birth defects surveillance, medical training, and awareness efforts(Dolk et al, 2021) equal opportunity and reduce inequalities of outcome, including by eliminating discriminatory laws, policies and practices and promoting appropriate legislation, policies and action in this regard • Birth defects are associated with various socio-demographic inequalities(Deguen et al, 2016) …”
mentioning
confidence: 99%